CNN-BASED ARTIFICIAL INTELLIGENCE (AI) IMPLEMENTATION TO IDENTIFY BASMATI RICE IN SUBANG DISTRICT - Masriwilaga, Ari ajibekti; wibowo, ari; susanto, dian (Jurnal Mekanika dan Manufaktur, 2023)
The existence of Basmati rice among the upper middle class in Indonesia is increasingly popular. Unfortunately, this rice is only grown in northern India and Pakistan. Fulfillment of rice must be imported and the price in Indonesia is relatively expensive. Responding to this phenomenon, the Center for Rice Research (BB Padi), the Agricultural Research and Development Agency succeeded in assembling a special rice variety Basmati. And given the name Baroma, an abbreviation of type Basmati Aromatic rice. And Baroma rice was launched in Subang in 2019 until now it has been recorded that several agricultural lands in Subang have planted this type. The more types of rice varieties, the more types of rice will be found. So that it will make consumers difficult to distinguish between types of rice with one another. Therefore, we need a solution to overcome this problem. And one solution that can be used is to use AI technology, as in the research we did. Using the CNN algorithm produces very good accuracy for detecting types of rice such as the type of data used for training data and test data. From the results of the model training carried out, it produces an accuracy rate of 98,52% while model testing to see how well the model predicts the label correctly is 97,80%.